The Dawn of Geostationary Air Quality Monitoring: Case Studies From Seoul and Los Angeles - Judd, Laura M.; Al-Saadi, Jassim A.; Valin, Lukas C.; Pierce, R. Bradley; Yang, Kai; Janz, Scott J.; Kowalewski, Matthew G.; Szykman, James J.; Tiefengraber, Martin; Mueller, Moritz (Frontiers in Environmental Science, 2018)
With the near-future launch of geostationary Earth orbit (GEO) pollution monitoring satellite instruments over North America, East Asia, and Europe, the air quality community is preparing for an integrated global atmospheric composition observing system at unprecedented spatial and temporal resolutions. One of the ways that NASA has supported this community preparation is through demonstration of future space-borne capabilities using the Geostationary Trace gas and Aerosol Sensor Optimization (GeoTASO) airborne instrument. This paper integrates repeated high-resolution NO2 maps from GeoTASO, ground-based Pandora spectrometers data, and low Earth orbit (LEO) measurements from the Ozone Mapping and Profiler Suite, for case studies over two regions: the Seoul Metropolitan Area, South Korea on June 9th, 2016 and Los Angeles Basin, California on June 27th, 2017. This dataset provides a unique opportunity to illustrate how GEO air quality monitoring platforms and ground-based remote sensing networks will close the current spatiotemporal observation gap. In both areas, the earliest morning maps exhibit spatial patterns similar to emission source areas (e.g., urbanized valleys, roadways, major airports) and change later in the day due to boundary layer dynamics, transport, and/or chemistry. On June 9th, 2016, GeoTASO observes NO2 accumulating within the Seoul Metropolitan Area, while NO2 peaks in the morning and decreases throughout the afternoon in the Los Angeles Basin on June 27th, 2017. The nominal resolution of GeoTASO is finer than will be obtained from GEO platforms, but when NO2 data over Los Angeles are up-scaled to the expected resolution of TEMPO, spatial features discussed are preserved. Pandora instruments installed in both metropolitan areas capture the diurnal patterns observed by GeoTASO, continuously and over longer time periods and will play a critical role in validation of the next generation of satellite measurements. These case studies demonstrate a diversity of diurnal patterns in two urbanized regions and associates them with meteorology or anthropogenic patterns, hinting at the spatial and temporal richness of the upcoming GEO observations. LEO measurements, despite their inability to capture the diurnal patterns at fine spatial resolution, will be essential for intercalibrating the GEO radiances and cross-validating the GEO retrievals in an integrated global observing system.